Grado de competitividad del comercial “Todo x 50” del cantón Vinces en el periodo 2024. - Triguero Arévalo, José Aldo (2024)
The objective of this study is to analyze the degree of competitiveness of the commercial “TODO X 50” located in Vinces, period 2024, which revealed several factors such as: the constant innovation of the competition that represents a challenge, which forces the business to update its products and services to remain in force. In addition, limitations in personnel training affect operational efficiency and the ability to adapt to market demands. The study, based on a mixed approach, included interviews with the manager and customer surveys. The results showed that the perception of the variety of products and prices is mostly positive, although there are areas for improvement in customer service, corporate image and product organization, as well as the need to implement loyalty strategies and more frequent promotions to attract new customers. It was concluded that the competitiveness of the commercial sector faces the challenge of being constant in the innovation of its products and services. In addition, poor staff training affects business performance, which is a challenge for its commercial strategy.